Peran Penyuluh Agama Islam dalam Penguatan Moderasi Beragama di Kabupaten Mandailing Natal - Muhammad Iqbal; Mohd. Rafiq; Anas Habibi Ritonga (Ittishol: Jurnal Komunikasi dan Dakwah, 2024)
Indonesia's vast population diversity includes various ethnicities, tribes, customs, cultures, languages, and religions. Religious moderation is a crucial agenda for every citizen to achieve peaceful coexistence among religious communities. As a fundamental value of every religion, strengthening moderation is a program aimed at fostering moderate attitudes and thinking among society. This research aims to explore the reinforcement of religious moderation values through the role of Islamic religious counselors in the Office of Religious Affairs in Mandailing Natal Regency. This research utilizes descriptive qualitative research, specifically field research, which collects data from the field. Data collection methods include interviews with 16 Islamic religious counselors, 4 heads of the Office of Religious Affairs, and 1 officer in charge of Zakat and Waqf management. Observations were conducted at 4 locations to observe the routine religious guidance activities conducted by Islamic religious counselors. Other data sources were obtained from relevant documents. Data were analyzed inductively through data reduction, data classification, data presentation, analysis, and drawing conclusions. The results of this study indicate that Islamic religious counselors play a strategic role in strengthening religious moderation in Mandailing Natal Regency. They are essential factors in strengthening understanding of religious moderation among the community through guidance and counseling activities. The materials delivered by counselors in guidance and counseling activities include worship and transactions, teaching good social life, understanding of wasatiyyah or balance, and obedience in practicing religious teachings properly. Religious counselors play roles as informative and educational, consultative, advocative, mediative, and facilitative. Their role in strengthening religious moderation is dominated by informative and educational roles to instill religious moderation values for the realization of a moderate society. Counselors play a strategic role through various activities such as routine religious gatherings, Friday sermons, guidance of study circles, large-scale religious gatherings, religious activities in correctional institutions, content creation on social media, and nurturing religiously moderate villages. This study recommends further research to measure public interest in religious moderation from different perspectives.